INVESTIGATING THE IMPACT OF PATIENT-CENTERED COMMUNICATION ON MEDICATION ADHERENCE AMONG CHRONIC DISEASE PATIENTS IN HAFAR ALBATIN - Meshari Jalawi Habib Aldhafeeri, Abdulaziz Rhial Awad Aldhafeeri , Munifah Jalawi Habib Aldhafeeri, Hasnah Awadh Saud Almutairi, Khaled Salem Haji Al-Shammari, Hamoud Marzouq Hamdan Al-Shammari, Bdour Malfi Alharbi, Maryam Malfi Alharbi , (Chelonian Research Foundation, 2022)
Patient-centered communication is a key factor in promoting medication adherence among chronic disease patients. This study aims to investigate the impact of patient-centered communication on medication adherence among chronic disease patients in Hafar AlBatin, Saudi Arabia. A mixed-methods approach was employed, involving a survey of 200 chronic disease patients and semi-structured interviews with 20 healthcare providers. The survey assessed patients' perceptions of patient-centered communication, medication adherence, and demographic characteristics using validated scales. The interviews explored healthcare providers' perspectives on the challenges and best practices in promoting patient-centered communication and medication adherence. The findings revealed a significant positive relationship between patient-centered communication and medication adherence (r=0.75, p<0.001). Patients who reported higher levels of patient-centered communication were more likely to adhere to their medication regimens. The study highlights the importance of fostering patient-centered communication in healthcare settings to improve medication adherence and patient outcomes among chronic disease patients in Hafar AlBatin. Keywords: patient-centered communication, medication adherence, chronic diseases, nursing, Saudi Arabia